FINANCIAL ANALYSIS FOR BANDUNG SKYBRIDGE PROJECT - RACHMAWATI (NIM: 29110344) Pembimbing : Ir. Subiakto, MBA, IMA
Congestion is frequently occured in big cities, this problem occurs due to the high number of vehicles but less roads available. Congestion is also occured in Bandung, particularly on the holiday. As one of tourist destinations in West Java, Bandung has been visited by many tourist. The number of tourists is increasing and it is more difficult to avoid congestion.In order to support Bandung Tourism, congestion problem should be overcome immediately, so that the tourist could enjoy their holiday more convenient. Therefore, Bandung has proposed to establish a means of mass transportation, that is cable car and the project is Bandung SkyBridge.In this final project, the author try to provide another insight to PT. Aditya Dharmaputra Persada as developer of Bandung SkyBridge Project about the financial aspect of this project. This financial analysis is using several financial performance measurements. This final project also performed simulations by using Crystal Ball application to identify which component that most sensitive to NPV and IRR and how is the probability to generate desired return. Moreover the thesis perform stress test, to know how sensitive of those componentsto IRR and NPV.Based on the result of financial assessment, the project is profitable and feasible to be executed. The result of assessment are as follow: PBP 5,44; NPV Rp1.021.122.687.283; IRR 35,63%; PI 4,14; ROI 23,36%; ROE 66,74%, BBP 36%. Probability to generate NPV is 49,97% and the probability to obtain 35,63% IRR is 50,97%. The sensitive components to NPV are ticket price and WACC, while the sensitive component to IRR are ticket price and forecasted passengers.The project is quite strong, ticket price as a sensitive component to NPV and IRR is allowed to be reduced.